ERITREAN ELEMENT: AN OVERVIEW OF THE RELATIONSHIP BETWEEN ERITREA AND LTTE DURING THE SRI LANKAN CIVIL WAR - Amarasinghe, Punsara (Journal of Terrorism Studies, 2024)
The timely imperative of identifying these links is rooted in understanding how external factors assisted one of the most advanced terrorist organizations in the world to accomplish its task. Furthermore, this paper discusses two path dimensions of LTTE-Eritrean relations by examining arm trade and logistics support given by Asmara to LTTE. Furthermore, this paper discusses two path dimensions of LTTE-Eritrean relations by examining arm trade and logistics support given by Asmara to LTTE. The emerging results from this paper prove the Bush administration's hypothesis of describing Eretria as a state sponsor of terrorism along with North Korea.